A Myopic Normative Database for Retinal Nerve Fiber Layer Thickness Using Optical Coherence Tomography. Issue 10 (20th July 2022) - Yilmaz, Hayati; Yeşiltaş, Yağmur Seda; Aydemir, Emre; Aksoy Aydemir, Gözde; Gökgöz Özişik, Gülce; Koylu, Mehmet Talay; Cagatay, Caglar; Bayer, Atilla
Abstract : Précis: The purpose of this study was to determine changes in optical coherence tomography (OCT) color codes after applying a myopic normative database. The diagnostic performance of the retinal nerve fiber layer analysis improved with the use of this database. Purpose: To evaluate the peripapillary retinal nerve fiber layer (pRNFL) OCT color codes based on a newly generated myopic normative database in comparison to the built-in normative database. Materials and Methods: A total of 371 subjects were included in this validation study in an attempt to generate a myopic normative database. Eighty myopic glaucomatous and 80 myopic healthy eyes were evaluated to determine the diagnostic performance of this database. The distribution of the color codes was investigated among the groups with reference to the built-in and myopic normative databases, and the 2 databases were compared in terms of abnormal color code frequency. The diagnostic performance of the myopic database was presented with sensitivity, specificity and area under the receiver operating characteristic curve values. Results: The agreement between the databases decreased with increasing myopia degree. The distribution of the color codes of the built-in software significantly differed among the study groups in all sectors ( P =0.009 for the temporal sector and P <0.001 for the remaining sectors). When the myopic database was used, there were no longer significant differences among the groups for the temporosuperior, temporoinferior, temporal, and nasal sectors ( P =0.561, 0.299, 0.201, and 0.089, respectively). After applying the myopic normative database, the specificity of the pRNFL color codes increased from 70.1% to 90.2%, and the area under the receiver operating characteristic curve value from 0.851 to 0.945. Conclusions: The use of a myopic normative database for pRNFL using SD-OCT significantly decreased differences among myopia severity groups, and may help to more reliably assess glaucoma in myopic eyes.